2019
DOI: 10.1111/jocn.14789
|View full text |Cite
|
Sign up to set email alerts
|

Self‐stigma among Korean patients with diabetes: A concept analysis

Abstract: Aims and Objectives To conduct a concept analysis of self‐stigma among patients with diabetes and introduce an operational definition of self‐stigma. Background Due to fears of being monitored, patients with diabetes often conceal their disease and/or withdraw from social relationships. These behaviours negatively affect patients’ self‐care and socialisation. Design A concept analysis was conducted using a three‐phase (theoretical phase, fieldwork phase and final analysis phase) hybrid method by Schwartz‐Barco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 59 publications
1
33
1
Order By: Relevance
“…The initial question of the DSSS was developed based on the definition, dimensions and attributes obtained during concept analysis of self‐stigma for diabetes (Seo & Song, 2019). Results of concept analysis revealed that the scale was composed of nine attributes in three dimensions: affective, cognitive and behavioural factors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The initial question of the DSSS was developed based on the definition, dimensions and attributes obtained during concept analysis of self‐stigma for diabetes (Seo & Song, 2019). Results of concept analysis revealed that the scale was composed of nine attributes in three dimensions: affective, cognitive and behavioural factors.…”
Section: Resultsmentioning
confidence: 99%
“…The self‐stigma concept included three categories with nine attributes: affective (negative feelings and feeling sorry for others who have concerns about me), cognitive (low self‐esteem and self‐ efficacy, perceived weakness, low expectations for the future, worry for children and disease burden) and behavioural (social withdrawal and avoiding disease disclosure) factors. Detailed methods and results can be found in our main published paper (Seo & Song, 2019). Based on this, 40 questions were derived using existing self‐stigma tools and in‐depth interview data of patients with diabetes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…When people with a COVID-19 infection in our study described how the illness interfered in ordinary social relationships, stigma might be present as they, during the period of illness, were marked as different special cases and are thereby not able to meet ordinary social requirements. A recent research study has, however, described how individuals may try to reduce stigma by acting as normal or selectively disclosing their stigmatized attributes (Seo & Song, 2019).…”
Section: Comprehensive Understanding and Discussionmentioning
confidence: 99%